AN ANALYSIS OF CULTURAL AND LANGUAGE CONTENT IN ENGLISH TEXTBOOKS FOR THE THIRD GRADE STUDENTS OF JUNIOR HIGH SCHOOL - Oktariska, Fenia; Jismulatif, Jismulatif; Aruan, Rumiri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This research is aimed to find out what culture and how culture were implemented in English textbooks for third grade students of Junior High School. The data of this research were the English textbooks entittled Bahasa Inggris Think Globally Act Locally revised 2018, English in Focus for grade IX Junior High School and Bright an English Course for Junior High School revised edition. The sample in this research was word, pictures,illustrations, reading passages and other many activities in each textbooks. The data were collected by using a checklist format based on the framework from Cortazzi and Jin (1999). There are two aspects have been analyzed: Big C and little C. The findings of the research revealed that Source Culture was the most appeared in these three English textbooks as categories of culture, and Product was the most frequently appeared in these three English textbooks. As the result of research, it found that the textbook is more likely to promote our local culture ( Source culture) in learning English and make into product of culture rather than any aspect of categories of culture and elements of culture..Keywords: English Textbook, Junior High School, Cognitive, Psychomotor.